2019
DOI: 10.5937/ijcrsee1901063b
|View full text |Cite
|
Sign up to set email alerts
|

Optimum virtual environment for solving cognitive tasks by individuals with autism spectrum disorders: The questions and methods of design

Abstract: The number of people with autism spectrum disorders (ASDs) is growing in Russia and the world at large. It is important to find ways to diagnose and correct the work with such individuals. There is much evidence that children with ASDs often exhibit pronounced communicative difficulties, problems in establishing visual contact etc. Specialists working with this category of patients face serious difficulties in trying to find effective ways to interact with them. The use of virtual reality environments that hav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 12 publications
(10 reference statements)
0
1
0
Order By: Relevance
“…Ellis & Calvo, 2004) it can be concluded that learning assignments such as discussions are a valuable and meaningful way of learning. In virtual discussions that need to be paid attention to is the student's manipulative cognitive (Bystrova-Yurievna et al, 2019), as a result, critical thinking and HOTS can be achieved. Students who take an active role in discussions will be able to interpret learning messages and construct material.…”
Section: Discussionmentioning
confidence: 99%
“…Ellis & Calvo, 2004) it can be concluded that learning assignments such as discussions are a valuable and meaningful way of learning. In virtual discussions that need to be paid attention to is the student's manipulative cognitive (Bystrova-Yurievna et al, 2019), as a result, critical thinking and HOTS can be achieved. Students who take an active role in discussions will be able to interpret learning messages and construct material.…”
Section: Discussionmentioning
confidence: 99%